LENGTH-WEIGHT RELATIONSHIP AND CONDITION FACTOR OF Prochilodus nigricans AND Potamorhina altamazonica IN THE TAHUAYO RIVER BASIN, LORETO (PERU) - CAÑAS-ALVA, Carlos M. (2020)
In this study, it is presented the Length-Weight relationship and Condition Factor for Prochilodus nigricans (boquichico) and Potamorhina altamazonica (llambina) from the Tahuayo River basin. These two species are among the most important commercial and subsistence fishing resources for Loreto, Peru. Biological data were collected during 12 months and analyses were obtained after 1,114 individual records of these two species from catches provided by the Association of Artisanal Fishermen "Puma Garza I". Results showed that boquichico, both males and females, features an isometric growth (PT = 0,0126 × LT3.034) and llambina has a negative allometric growth with differences in the parameters for females (PT = 0,0985 × LT2.35) and for males (PT = 0,0755 × LT2.43). Fish stocks of both species were found in good fitness condition throughout the hydrological cycle and variations were related to the hydrological conditions of the basin. These estimates provide the first information about growth of these two species as a function of size and weight and will be very useful in the management of their fish stocks distributed in the Tahuayo River basin.